Effect of neuroprotective therapy with citicoline on the course of experimental non-infectious anterior and intermediate uveitis - Зборовська, Олександра Володимирівна; Зборовська, О. В.; Zborovska, Oleksandra V.; Горянова, Ільїна Сергіївна; Горянова, І. С.; Horianova, Ilina S.; Ульянов, Вадим Олексійович; Ульянов, В. О.; Ulianov, Vadym O.; Дорохова, Олександра Едуардівна; Дорохова, О. Е.; Dorokhova, Oleksandra E.; et al. (Poltava : SS AHET of Ukraine, 2024)
Non-infectious anterior and middle uveitis is a significant uveitis group, leading to decreased visual acuity and often blindness. The purpose of the study was to determine the features of the clinical course and morphological changes of the choroid, retina, and optic nerve in the early and late stages of experimental non-infectious anterior and middle uveitis under the conditions of neuroprotective citicoline therapy. We studied the clinical course of the disease and morphological changes on the 10–13th, and 33rd days after the administration of the provocative dose. The use of citicoline led to a decrease in inflammation in uveitis. First of all, due to reduced swelling of the cornea and iris. It was confirmed by histomorphological examination. It reduced the violation of the retinal cytoarchitectonic disturbances and degenerative and destructive changes in its neurons. It also reduced the swelling of the retina and optic nerve cells. It activated intracellular compensatory processes in the retina, particularly in the pigment epithelium and optic nerve glial cells. Неінфекційні передні та середні увеїти – це значна група увеїтів, що призводить до зниження гостроти зору, а нерідко і до сліпоти. Метою дослідження було визначити особливості клінічного перебігу та мофрологічних змін хоріоідеї, сітківки і зорового нерву на ранніх та пізніх строках перебігу експериментального неінфекційного переднього і середнього увеїту за умов нейропротекторної терапії цитіколіном. Вивчався клінічний перебіг захворювання та мофрологічні зміни на 10–13 та 33 добу після введення провокуючої дози. Застосування цитіколіну призвело до зменшення виразностізапалення при увеїті. В першу чергу за рахунок зменшення набряку рогівки та райдужної оболонки. Що підтверджується за допомогою гістоморфологічного дослідження. Це зменшення порушення цитоархітектоніки сітківки, дегенеративних та деструктивних змін її нейронів, зменшення набряку клітин сітківки і зорового нерва; активація внутрішньоклітинних компенсаторних процесів в сітківці, зокрема, в клітинах пігментного епітелію, а також в гліальних клітинах зорового нерву.
Zborovska O. V. Effect of neuroprotective therapy with citicoline on the course of experimental non-infectious anterior and intermediate uveitis / O. V. Zborovska, I. S. Horіanova, V. O. Ulianov et al. // World of Medicine and Biology. – Poltava : SS AHET of Ukraine, 2024. – 90(4). – P. 185-190. Режим доступу: https://hdl.handle.net/11300/32377
Keywords: anterior uveitis; intermediate uveitis; experimental animal model; choroid; retina; optic nerve; citicoline; передній увеїт; середній увеїт; експериментальна тваринна модель; судинна оболонка; сітківка; зоровий нерв; цитіколін